The comparative effect of onchocerciasis on the people of the northern and southern parts of Nigeria (2014)
Researchers have variously submitted that Simulium damnosum, the arthropod vector carrying the onchocerciasis parasite, breeds during the rainy season in the south western part of Nigeria. Since there is a difference in the climatic condition found in the northern part of Nigeria, we need to specially do a comparative study of situations in the North, as related to the disease, in terms of its causes and effects. This study investigated the differences in the North-South prevalence of onchocerciasis and the different types of the disease found in the North versus the South of Nigeria. The comparative strength (quality) of its impact and the spread of its impact. Local government records were accessed and a survey for presence of microfilariae in individuals carried out in Kaduna and Oyo states. Onchocerciasis in the north is more impactful health-wise and economically on the Northern population with higher frequency of occurrence of river blindness and a higher overall prevalence as well as in the productive age groups